Managing social media as destination marketing tool for tourism in Antique - Abao, Elijah; Armada, Natalia Beatriz; Bala, Fatima Nina; Barnuevo, Kristoffer; Gotera, Thea
Access to the internet has become significant, if not necessary, in the everyday lives of people around the world , so it is not surprising why it has been constantly and aggressively used by marketers. Social media has become one of the most effective tools to drive in tourists into uncharted tourist destinations. This phenomenon is captured in the increasingly popular social media platforms like dynamic, image-based and video-baed platforms. The fndings of our study show that the widely used conventional social media outlets such as 'Facebook', 'Twitter', 'Instagram', 'Pinterest', 'You Tube', etc. are very effective in promoting the aesthetic aspects of tourism indicators provided in this study such as tourist spots, events, cuisine, hospitality, price, tourist guide, purpose of travel, travel companion and work-life balance. Thus, it can influence the varied market of travellers, bloggers students, young professionals, adults and families. Furthermore, the findings of our study show that there is a direct influence of modern technologies like social media as marketing tool to promote tourist spots around the Province of Antique. For practical implication, comprehensive management implications for destination marketing were also discussed. From the gathered data which were analyzed quantitatively and qualitatively, it showed that most of the participants of this study are daily users of social media. it is also evident that majority of the respondents haave seen social posts which stirred positive interest for them to plan a trip to the province, to make them appreciate the province, or directly make them want to visit Antique. Although most of them agreed that they were able to obtain information about tourist destination from the different platforms of social media (dynamic, image-basedd and video-based), they also admitted that they also encountered problems in using the tool such as insufficient information and lack of timely site updates. Nevertheless, obtaining information from social media about the different tourist spots in Antique through personal testimony posts, photos and moving pictures influenced them to visit the place. However, majority of them would want to travel during summer time. They believe that taking vacation from work and studies have a positive impact in their work-life balance. The results of this study reveals that at this current age, modern strategies such as social media could be an effective tool in promoting a certain place ike the Province of Antique.